Designing diversity: ethical virtual agents for effective dermatological training - Kujević, Melisa; Schmitz, Michael; Akbal, Mert; Sassen, Corbin; Mergen, Marvin (Frontiers in Virtual Reality, 2025)
This paper discusses the importance of diversity and inclusivity in designing virtual agent simulations for dermatology. As virtual reality (VR) technology become increasingly utilized in dermatological diagnosis, treatment, and training, there is a need to ensure the agent representations reflect diverse populations. Our paper explains that virtual agents should represent a wide range of ethnicities, genders, skin tones, and other physical characteristics relevant to dermatology. It criticizes current classification schemas like the Fitzpatrick scale as lacking diversity, and encourages alternative approaches. Technical considerations in modeling diverse agents are explored, with popular tools analyzed for customization options and usability. Ethical issues around cultural sensitivity and stereotyping are highlighted as crucial to agent design. Examples are provided of how skin conditions may manifest differently across diverse populations, emphasizing why inclusive agents are vital for virtual simulations. Overall, the paper argues that comprehensive agent diversity is indispensable for achieving acceptance of VR in dermatology and accurately connecting virtual representations to real-world patients.